Pelatihan Menulis Teks Biografi Logis dan Kritis pada Siswa SMAN 1 Kota Malang - Daroe Iswatiningsih; Erna Yayuk; Sudiran; Ridho Covinda Wahyu Firmansyah (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2026)
Purpose – This community service activity aims to improve students writing literacy skills through training in logical and creative biography writing at SMAN 1 Kota Malang, while also producing sustainable literacy-based outputs for the school Design/methodology/approach – The program is designed using a participatory action-based training approach that combines a genre-based approach, the writing process, and project-based learning. Activities include conceptual training, guided writing exercises, in-person and online revision support, as well as the curation and publication of works in both print and digital ISBN-registered books Findings – The training demonstrated improvements in the quality of students’ writing in terms of text structure, logical chronology, integration of factual data, and linguistic creativity. The outcome a 256-page biography with an ISBN serves as evidence of the program’s success and has led to increased motivation to write, greater student confidence, and the strengthening of the school’s culture of literacy. Originality/value – The novelty of this programme lies in the integration of genre-based and process-based training with official publications as the school's collective literacy products. This model not only improves writing skills, but also builds a collaborative, documented literacy ecosystem that has the potential to be replicated in other schools.